2006
DOI: 10.1666/04069.1
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of the Neoselachii (Chondrichthyes) during the Jurassic and Cretaceous

Abstract: The Neoselachii are a monophyletic group including all of the extant sharks and rays. They underwent rapid diversification throughout the Jurassic and Cretaceous, going from low-di versity assemblages of members of extinct orders in the Late Triassic to diverse assemblages con taining representatives of most extant clades by the end of the Cretaceous. The known fossil record of Mesozoic neoselachians is composed largely of isolated teeth, with articulated skeletal remains being known from a limited number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 27 publications
4
118
0
1
Order By: Relevance
“…So far, 34 fossil Squatina species mostly based on isolated teeth have been described (Cappetta 2006). While Underwood (2002Underwood ( , 2006 considered the oldest representative to be of Kimmeridgian age, de Carvalho et al (2008) showed that Late Jurassic squatiniforms all belong to a different taxon, †Pseudorhina. All pre-Kimmeridgian records that have been variously assigned to Squatina were considered to belong to orectolobiforms by Underwood (2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, 34 fossil Squatina species mostly based on isolated teeth have been described (Cappetta 2006). While Underwood (2002Underwood ( , 2006 considered the oldest representative to be of Kimmeridgian age, de Carvalho et al (2008) showed that Late Jurassic squatiniforms all belong to a different taxon, †Pseudorhina. All pre-Kimmeridgian records that have been variously assigned to Squatina were considered to belong to orectolobiforms by Underwood (2006).…”
Section: Introductionmentioning
confidence: 99%
“…While Underwood (2002Underwood ( , 2006 considered the oldest representative to be of Kimmeridgian age, de Carvalho et al (2008) showed that Late Jurassic squatiniforms all belong to a different taxon, †Pseudorhina. All pre-Kimmeridgian records that have been variously assigned to Squatina were considered to belong to orectolobiforms by Underwood (2006). However, the squatiniform fossil record does not consist entirely of isolated teeth but includes several holomorphic specimens and skeletal remains from different stratigraphical ages throughout their evolutionary history.…”
Section: Introductionmentioning
confidence: 99%
“…This was followed by a species-level diversity decline at the J/K boundary, resulting from decreased origination rates and heightened extinction rates (Kriwet & Klug, 2008;Kriwet, Kiessling & Klug, 2009a). However, no major neoselachian clades went extinct at the J/K boundary, and their Early Cretaceous standing diversity was substantially higher than Late Jurassic levels (Underwood, 2006;Kriwet et al, 2009a;Kriwet, Nunn & Klug, 2009b;Guinot, Adnet & Cappetta, 2012;Klug & Kriwet, 2013). A recent study showed that nearly all major extant lineages of sharks were already present in the latest Jurassic or earliest Cretaceous, with the origins of Squaliniformes, Squatiniformes, Orectolobidae, Lamniformes, and Carchariniformes occurring immediately prior to the boundary, and the timing of diversification of multiple important sublineages intimately associated with the J/K boundary (Sorenson, Santini & Alfaro, 2014).…”
Section: (K) Fish Groupsmentioning
confidence: 99%
“…Samples from Mesozoic rocks (e.g. Underwood andWard 2004, Guinot et al 2013) have yielded teeth absent in coarser samples in mesh sizes of 355m. In these studies, finer mesh sizes only produced additional teeth of species present in coarser fractions.…”
Section: Bulk Samplingmentioning
confidence: 99%
“…In the subsequent century, improvements in knowledge of the diversity of fossil species, their taxonomic affinity and their palaeobiological context has dramatically changed our understanding of fossil chondrichthyan faunas (e.g. Underwood 2006, Guinot et al 2013. Whilst this improvement in knowledge is a global phenomenon, it is especially striking when the shark and ray faunas of Britain, which formed the basis for most of Woodward's work and provided a lot of Agassiz's type specimens are considered.…”
mentioning
confidence: 99%